Disfunção temporomandibular em adolescentes: confiabilidade e validade de um questionario para pesquisa populacional, caracterização epidemiológica de uma amostra e estudo de potenciais fatores de risco - Franco, Ana Lúcia [UNESP] (2013)
The aim of the present study was to test the portuguese version of the questions proposed by the American Academy of Orofacial Pain (AAOP) for the screening of temporomandibular disorders (TMD), as well as to verify the prevalence and to identify potential risk factors for this condition in adolescents, public school students from Araraquara city, São Paulo, Brazil. The diagnosis of TMD was conducted with the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD), taken as reference standard. The reliability of the questions was estimated through internal consistence, inter-item correlation and reproducibility analyses. For the validity, tests of sensitivity, specificity, predictive value, acuracy and ROC curves were conducted. The potential risk factors were assessed with questionnaires. For the epidemiologic characterization, we used descriptive statistics, chi-squares tests and odds ratio, adopting 5% of significance. The sample was composed by 1307 adolescents (56.8% girls, mean age 12.72 years old). Overall, 397 (30.4%) adolescents presented TMD according to the RDC/TMD, 330 (25.2%) consisted of painful TMD diagnoses. AAOP questions presented satisfactory reliability and validity for the screening of TMD, specially painful TMD. The sample presented a considerable TMD prevalence, especially of painful and muscle TMD, and the majority of studied potential risk factors associated with all painful TMD diagnoses. There was also a high prevalence of headache complaints, which comprised a potential risk fator for painful and cronic TMD of combined origin. We concluded that TMD was common among adolescents and many factors associated with its presence in the studied sample.